Selective Attenuation of Lightning‐Generated Whistlers at Extralow Frequencies: DEMETER Spacecraft Observations. Issue 10 (8th October 2018) - Záhlava, J.; Němec, F.; Santolík, O.; Kolmašová, I.; Parrot, M.; Kouba, D.
Abstract: Frequency‐time spectrograms measured by the Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) spacecraft (2004–2010, altitude about 700 km) at frequencies below 20 kHz sometimes contain lightning‐generated whistlers whose intensity is significantly reduced at specific frequencies. The frequencies of the reduced intensity vary smoothly over the event duration, forming apparent curves in frequency‐time spectrograms. Events at frequencies higher than the Earth‐ionosphere waveguide cutoff frequency were explained by the interference of the first few waveguide modes of lightning‐generated spherics propagating therein (Záhlava et al., 2015, https://doi.org/10.1002/2015JA021607 . Here we present an analysis of events observed at frequencies lower than about 1 kHz. Altogether, we analyze 263 events identified at the times when DEMETER operated in the burst mode. The vast majority of the events (95%) took place during the nighttime, and they occurred more frequently during spring/autumn than during winter/summer. We present an overview of event properties. Moreover, measurements of all six electromagnetic field components performed by DEMETER allow us to perform a detailed wave analysis. It is shown that the emissions propagate with high wave normal angles inclined toward the Earth. We suggest that the events might be due to the wave propagation in the ionospheric waveguide formed around the refractive index maximum at the altitude of about 105 km. Key Points: We analyze ELF events formed by lightning‐generated whistlers with intensity significantly reduced at specific frequencies We perform a study of 263 events identified in the DEMETER spacecraft data, including their detailed wave analysis We suggest that the events might be created in the waveguide formed around the refractive index maximum in the lower ionosphere